Human rights and community-led development : lessons from Tostan - Cislaghi, Ben (Edinburgh : Edinburgh University Press, 2018)
This book investigates work of the NGO Tostan as a working model of human development. The study is grounded in the ethnographic study of the actual change that happened in one West African village.
Chapter 7 Dynamics of Social Change: A Model for Indirect Development PractitionersChapter 8 Conclusion; Notes; References; Index
Previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Online resource; title from home page (viewed on September 4, 2018).
eBooks on EBSCOhost
Keywords: Tostan (Organization : Senegal); Tostan (Organization : Senegal); Human rights; Community development; Droits de l'homme (Droit international); Développement communautaire; community development; LAW -- International; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Community development; Human rights